Characteristics of organic titanate modified titanium dioxide nanoparticles and its dispersibility in acrylic emulsion coating. (3rd November 2022) - Chinh, Nguyen Thuy; Mai, Tran Thi; Hung, Dao Phi; Hiep, Nguyen Anh; Trang, Nguyen Thi Thu; Trung, Tran Huu; Thai, Nguyen Xuan; Toan, Dao Huu; Binh, Dinh Thi My; Hoang, Thai
Abstract: This work presents the characteristics of rutile TiO2 nanoparticles modified by isopropyl tri[di(octyl) phosphato] titanate (KR‐12) with the content of 3, 5 and 10 wt.% as compared to TiO2 nanoparticles weight. The infrared (IR) spectroscopy, scanning electron microscopy (SEM), dynamic light scattering (DLS), and thermal gravimetry analysis (TGA) methods were used to evaluate the surface modification efficiency of the TiO2 nanoparticles with KR‐12. The TGA and IR analysis results indicated that the organic coupling agent (KR‐12) was grafted to the surface of the nanoparticles. The TiO2 nanoparticles after modification could disperse stably in water easily. The modification caused the shift of surface charge of the TiO2 nanoparticles to more positive region. The average particle size of TiO2 nanoparticles modified with 0, 3, 5, and 10 wt.% of KR‐12 was 443.9 nm, 295.3 nm, 334.8 nm, and 392.3 nm, respectively. The hydrophobic ability of TiO2 nanoparticles was improved significantly after modification. The modified TiO2 nanoparticles could well disperse in acrylic emulsion coating with dispersed phase size of 200‐400 nm. Abstract :